A District Policy for Counselling Services: A Process Guide - Armstrong, Robert B.; Young, Richard A.; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper describes the process used to develop and the content of a guide fordeveloping and implementing a district policy for school counselling service inBritish Columbia. Several unique features include: the composition and sponsorshipof the committee, the process rather than prescriptive nature of the Guide itself,and its utility for a wide range of professionals involved in school counselling services.